If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6X + -5y + -1y = 0 Combine like terms: -5y + -1y = -6y 6X + -6y = 0 Solving 6X + -6y = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '6y' to each side of the equation. 6X + -6y + 6y = 0 + 6y Combine like terms: -6y + 6y = 0 6X + 0 = 0 + 6y 6X = 0 + 6y Remove the zero: 6X = 6y Divide each side by '6'. X = y Simplifying X = y
| 2b-4-12b-9= | | 2x-4-16=0 | | 8h-h-7h= | | 5w+1w+6w= | | (X-3y+3)dx+(3x+y+9)dy=0 | | v^2/3-9v^1/3=-20 | | Lgx=1+3lgx | | 0.613=log(x) | | 6x+11+8x-7=180 | | x^2-60x+910=0 | | x^2-60x+190=0 | | 26+x=12 | | 2x-(4x-3/3)=1/2(3x-1) | | 48=6/y | | x(x-7)(x+13)=0 | | 4w+3=23 | | y=3+(ln^2)*x | | 5(-x-4)=30 | | x^2+2=2x+2 | | 71=35+(x*.18) | | 2x-c^2=0 | | 41=35+(x*.18) | | 80+1x+109=180 | | 6c-3+5(c-4)+2=4c+7(c-3) | | 4x-3-3x-2-x=10 | | 7x+30y=-7 | | (7+x)*(4+x)=100 | | (7x+1)(7x-1)-49(x+1)=4-98x | | x^2+6x^3+2x^2=0 | | x^2-1/3-x | | x^2-1/3-c | | 12+4x+3+7x= |